Identify Chemical Compounds of Wedelia biflora and Test Their Bioactivity as Antiplasmodium Berghei - M. Isa (Jurnal Medika Veterinaria, 2014)
The aims of the research is to identify chemical compounds of leaf Sernai (Wedelia biflora) and test their bioactivity as antiplasmodium against of Plasmodium berghei. Extraction of the compounds from the Wedila biflora leaf was done with methanol. To observe the bioactivepotency of the Wedelia biflora extract antiplasmodium test against with The 4-day test method was done. The Phytochemical test results using theLieberman-Burchard reagent positive for triterpenoids compounds and analysis by GC-MS chromatogram identified 45 compounds with anabundance peak maximum of 27.92% which is identified in the data base as kaur-16-en-18-oic acid. Wedelia biflora leaf extract potentiallyactive as antiplasmodium with IC values = 39.952 mg / kg BW.____________________________________________________________________________________________________________________Key words: antiplasmodium, GC-MS, Plasmodium berghei, Wedelia bifolra 50